The methodology of setting up and the management of antibiotic treatments in veterinary medicine - Anca Marculescu (Medicamentul Veterinar, 2007)
Antibiotic therapy represents one of the most frequently used methods in medical practice, human or veterinary. The efficiency of this therapy is based on an appropriate choose of antibiotics, avoiding also the errors that may occur by their utilization. Sometimes, the association of antibiotics is recommended, in order to reduce the antibiotic resistance and also to increase the efficacy of antibiotics in veterinary practice.